Study on the mechanisms of action of berberine combined with fluconazole against fluconazole-resistant strains of Talaromyces marneffei - Kai-su, Pan; Hong, Luo; Dong-yan, Zheng; Yan-qing, Zheng; Andrianopoulos, Alex; Latgé, Jean-Paul; Cun-wei, Cao (Frontiers in Microbiology, 2022)
Talaromyces (Penicillium) marneffei(T. marneffei) is a thermally dimorphic fungus that can cause opportunistic systemic mycoses. Our previous study demonstrated that concomitant use of berberine (BBR) and fluconazole (FLC) showed a synergistic action against FLC-resistant T. marneffei (B4) in vitro. In this paper, we tried to figure out the antifungal mechanisms of BBR and FLC in T. marneffei fluconazole-resistant. In the microdilution test, the minimum inhibitory concentration (MIC) of FLC was found 256μg/mL to 8 μg/mL and with fractional inhibitory concentration index (FICI) 0.28 in B4. After the treatments of BBR and FLC, the studies revealed that (i) increase reactive oxygen species (ROS), (ii) reduce ergosterol content, (iii) destroy the integrity of cell wall and membrane, (iv) decrease the extracellular rhodamine 123 (Rh123) via inhibiting efflux transporters, (v) decreaese the expression of genes AtrF, MDR1, PMFCZ, and Cyp51B however ABC1 and MFS change are not obvious. These results suggested that berberine has an inhibitory effect on T. marneffei and in combination with fluconazole can reverse the susceptibility of fluconazole-resistant strains to fluconazole, providing a theoretical basis for the use of berberine in the treatment of T. marneffei which may open up a new treatment option for T. marneffei infections.